2017
DOI: 10.1515/fhort-2017-0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of type and concentration of sugars, supplemented with 8-hydroxyquinoline sulphate, on the vase life of waxflower

Abstract: A study was conducted to test the effect of 58.5 mM maltose, glucose, fructose, galactose and sucrose, and sucrose concentrations of 14.6, 29.2, 58.5 and 117.0 mM supplemented with 200 mg L -1 8-hydroxyquinoline sulphate (HQS) on the vase life and stem fresh weight changes in waxflower (Chamelaucium Desf.). The effect of the interaction between sucrose and HQS concentrations on the vase life of the cultivar 'Alba' was also investigated. All the types of exogenous sugar significantly increased the vase life of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…An innovation thatutilised an electrochemically treated solution containing potassium chloride, hypochloric acid and dissolved oxygen, into which cut flower stems were inserted, improved their quality and vase life (Abdolahi et al, 2013). Anumber of chemical treatments have been used to improve cut Gladiolus quality parameters (Bhat and Sheikh, 2015), while a similar fate was accomplished in some ornamental plants treated with preservative solutions containing glycerol and surfactants (Dung et al, 2017). The objective of this study was to evaluate the effect of pulsing and wet cold storage on the starch and sugar biomarkers on cut Gladiolus (Gladiolus grandiflorus L. cv.…”
Section: Introductionmentioning
confidence: 99%
“…An innovation thatutilised an electrochemically treated solution containing potassium chloride, hypochloric acid and dissolved oxygen, into which cut flower stems were inserted, improved their quality and vase life (Abdolahi et al, 2013). Anumber of chemical treatments have been used to improve cut Gladiolus quality parameters (Bhat and Sheikh, 2015), while a similar fate was accomplished in some ornamental plants treated with preservative solutions containing glycerol and surfactants (Dung et al, 2017). The objective of this study was to evaluate the effect of pulsing and wet cold storage on the starch and sugar biomarkers on cut Gladiolus (Gladiolus grandiflorus L. cv.…”
Section: Introductionmentioning
confidence: 99%
“…Solution balance in cut spikes was changed when there was an imbalance in solution uptake and transpiration rate (Ha et al, 2017). The reason for the change in imbalance was a high concentration of sucrose that causes osmotic stress in flowers (Dung et al, 2017) along with increase microbial multiplication that leads to xylem vessels blockage (Yagi et al, 2014). Results related to the response of different gladiolus cultivars towards preservative solutions vary from variety to variety.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown importance of sugar in flower opening and its vase life (Dung et al, 2017;Cavasini et al, 2018;Gómez-Merino et al, 2020). The accumulation of sugars in petal cells decreases the water potential, thus promoting water influx, which likely leads to cell enlargement and flower opening (Van Doorn and Kamdee, 2014).…”
Section: Cultivarmentioning
confidence: 99%